Zinc and cobalt complexes with (2-carboxyphenoxy) acetic acid ligand: syntheses, structures, fluorescent and magnetic properties. Issue 17 (1st September 2016) - Li, Jun-Xia; Du, Zhong-Xiang
Abstract: Four binary compounds, [Zn(cpa)(H2 O)3 ] (1 ), [Co(cpa)(H2 O)3 ] (2 ), [Zn(cpa)(H2 O)]n, (3 ) and [Co(cpa)(H2 O)]n (4 ) (H2 cpa = (2-carboxyphenoxy)acetic acid), have been synthesized and structurally characterized. In mononuclear1 or2, the metal ion (Zn II for1 and Co II for2 ) is surrounded by three water molecules and one tridentate chelate cpa 2− in a distorted octahedral geometry, while in3 or4, the central metal ion (Zn II for3 and Co II for4 ) is located in a deformed square–pyramid formed by one water and two cpa 2− . Each cpa 2− is chelate bridging μ 2 coordination and forms a 1-D zigzag chain structure2 or3 . The different synthesis conditions for1 –4 have been carefully discussed. The solid-state fluorescence measurements for1 and3 together with magnetic properties for4 also have been investigated. Abstract :